Ferroptosis and its relationship with cancer - Su, Chuanchao; Xue, Yiwen; Fan, Siyu; Sun, Xin; Si, Qian; Gu, Zhen; Wang, Jingfei; Deng, Runzhi (Frontiers in Cell and Developmental Biology, 2025)
Marked by iron buildup and lipid peroxidation, ferroptosis is a relatively new regulatory cell death (RCD) pathway. Many diseases like cancer, myocardial ischemia-reperfusion injury (MIRI), neurological disorders and acute renal failure (AKI) are corelated with ferroptosis. The main molecular processes of ferroptosis discovered yet will be presented here, along with the approaches in which it interacts with tumour-associated signaling pathways and its uses in systemic therapy, radiation therapy, and immunotherapy managing tumors.